6th Annual Fresno County Young Lawyers Association Justice Hopper Memorial Luncheon; Speaker: San Francisco Superior Court Judge Ira Brown - Watkins, Howard::::::::: (1987)
Robert Sears speaking at lectern about Justice Hopper; seated: Howard Sagaser, Justice Donald Franson and ?